Challenges of Design Education in Malaysia: Implementation Teaching and Learning - Ahmad, Norliza; Abd Rahman , Khairul Aidil Azlin; Sharif, Roslina (International Journal of Psychosocial Rehabilitation, 2020)
The Malaysian Education Development Plan (MEB) 2013-2025 has recently reported nine indicators of teaching and learning approaches that teachers can use in various fields including in design education. The teaching and learning approaches in the curriculum report are self- learning, collaborative, project-based, inquiry based, problem-based, mastery learning, constructivism, exploration, observation and science, technology, engineering and mathematic (STEM). This studied aims to identified teaching and learning implementation among design teachers in Johor, Malaysia based on the newly introduced curriculum in Malaysia. In addition, this studied aims to addressed the problems faced by design teachers and in implementing project based learning. The total number of respondents involved is 17 teachers who are teaching the Design subjects in 2017 and 221 Form Four (Age 16) students. Data collection was conducted through questionnaire and interview. Furthermore, the data were analysed by descriptive statistical techniques. Meanwhile, the finding of the problems obtained from the interviews among teachers and students were translated into appropriate group indicators. Then, the indicator is used as the starting point for organizing the instrument items in the form of a statement tables. The finding shows that the teaching and learning strategy of the Form Four (age 16) used by the teachers is Project-Based Learning (PBL). The implementation in Form Four teaching and learning also shows that the process of creating and designing various ideas was the most difficult process by referring to the problems of creativity in creating a product in a project-based learning (PBL) conducted in secondary schools.